Virtual system for early detection of COVID-19 infection "Etaware-CDT-2020 prototype design" (corroborated by rRT-PCR data). (March 2022) - Etaware, Peter Mudiaga
Graphical abstract: Highlights: Etaware-CDT-2020 will increase the chances of early detection of the deadly COVID-19 infection, by way of providing the populace with personal detection tools that can be stored on their electronic gadgets, in order to increase the chances of the COVID-19 detection. Furthermore, Etaware-CDT-2020 is unique such that it can be used anywhere and anytime by anyone. Abstract: The 2nd phase of COVID-19 infection outbreak experienced worldwide is an attestation to the decline in the efficiency of COVID-19 detection kits available worldwide. rRT-PCR still remains the best confirmatory test for COVID-19 infection. Sadly, most medical professionals are not conversant with the rRT-PCR protocols. Therefore, more easy-to-use alternatives are required as backup, to compensate for these lapses. "Etaware-CDT-2020" is a virtual system designed for early detection of COVID-19 infection. A comparative COVID-19 diagnosis was conducted using Etaware-CDT-2020, corroborated by rRT-PCR-confirmed COVID-19 results obtained from China (Latitude 35.8617 o N and Longitude 104.1954 o E), which was the epicentre for COVID-19 infection outbreak. A cross-comparison of results showed that there was a positive correlation between the output result from Etaware-CDT-2020 and rRT-PCR diagnosis from Wuhan (r = 0.92) and Hubei (r = 0.97). Furthermore, there was no significant difference between the diagnostic results of "Etaware-CDT-2020" and rRT-PCR, when compared by T-test (P(t = 0) > 0.05) and Pearson's Chi-Square test (0.04 ≥ P ≤ 0.12). Etaware-CDT-2020 is unique and can be used anywhere, anytime and by anyone. It is accessible, affordable, easy to install, simple to understand and user friendly.